Clusterization as direction of recreational tourist development of Podilsk region of Ukraine - Parfinenko, Anatolij; Bosenko, Karyna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article deals with the research of the potential of tourist clustering in Podilsk region of Ukraine. The formation of an effective regional tourism policy becomes especially relevant in the context of the greatly untapped potential of the tourism industry in most of the macroregions of our country. Tourist clusterization is a special form of internal integration and cooperation that can ensure high competitiveness of the region and improve its socio-economic status. The author analyses the advantages of the cluster approach to the management of destinations in Podilsk region, which are based on a combination of cooperation and competition in order to obtain a synergistic economic effect from the activity